PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG GO PUBLIK DI BURSA EFEK INDONESIA - Rimbano, Dheo (Universitas muhammadiyah palembang, 2013)
This study investigates the impact of firm financial performance on stock price which is concluched on the banking industry list in the Indonesian Stock Exchange. The length of the study is eight months. The sample usedin this study is 13 firms and variables used are EPS, PER, DPR, ROE, and ROA. The data obtained from Indonesian Stock Exchange. Ordinary Least Square (OLS) is employed in this study. The result reveal that apart from EPS, PER DPR, ROE have no significant impact on stock price.